Employment Discrimination in a Former Soviet Union Republic: Evidence from a Field Experiment - Muhammad Asali; Norberto Pignatti; Sophiko Skhirtladze (Institute of Labor Economics (IZA), 2017)
We provide the first experimental evidence about ethnic discrimination in the labor market in Georgia. We randomly assign Georgian and non-Georgian, male and female, names to similar resumes and apply for jobs as advertised in help-wanted web sites in Georgia. We find that gender has no effect on the probability of callback, but a job applicant who is ethnic Georgian is twice more likely to be called for a job interview than an equally skilled ethnic non-Georgian (Azeri or Armenian). The almost 100% gap in callbacks is statistically significant and cannot be abridged by having more experience or education. Both taste-based discrimination and statistical discrimination models are consistent with the evidence provided in this study. Labor market discrimination tends to aggravate in economic busts.
Keywords: J15; J71; C93; P23; 330; employment discrimination; field experiment; former Soviet Union; business cycles